The Influence of the Mind Mapping Model on Students’ Learning Outcomes in Biology Learning at Class XI in Tumou Tou Christian High School, Bitung City - Lolaro, Egrina; Roring, Verawati Ida Yani; Nanlohy, Fanny Nella (Jurnal Ilmiah Mandala Education (JIME), 2024)
Based on the results of observations and interviews with class This research aims to find out whether the mind mapping model can improve student learning outcomes in plant tissue material in class XI Tumou Tou Christian High School. This research uses a quasi-experimental method (quasi-experiment). The subjects of this research were class XI-A as the experimental class and class XI-C as the control class. Both classes will be given learning outcomes tests in the form of pretest and posttest. Based on the results of data analysis, the results showed that there was an influence of the mind mapping model on student learning outcomes in plant tissue material in class XI Tumou Tou Christian High School. This is based on the results of the t test using IBM SPSS for Windows if the Sig. (2-tailed) < Research Alpha (0.05), namely 0.00 <0.05, then H0 is rejected and H1 is accepted. This shows that there is an influence of applying the mind mapping model on improving student learning outcomes in plant tissue material in class XI Tumou Tou Christian High School.